THE EFFECT OF ZIG-ZAG TRAINING ON DRIBBLING ABILITIES - Prayois, Rada; Iyakrus, Iyakrus; Yusfi, Herri (Universitas Negeri Medan, 2023)
This study aims to determine the effect of zig-zag run training on the results of ball dribbling agility of the Academy Women Bigreds Palembang futsal club players. The method used in this research is a quasi-experimental method. The research design used was a one group pretest-posttest design. Sampling used a total population sampling technique with a sample of 35 people. The research instrument is a dribbling zig-zag. The results of data processing and analysis using the data normality test and hypothesis testing with the t-test formula, that the zig-zag exercise affects the results of futsal players' dribbling agility. This can be seen from the results of data analysis through the calculation of the t test formula with the t count criteria greater than t table (21, 136 ˃ 1,699) with a confidence level of 0.95 (α = 0.05) and the number of samples (N = 30), The proposed hypothesis is accepted. The zig-zag exercise really has an effect on the results of futsal players' ball dribbing agility. The implication of this research is that the zig-zag exercise has a significant effect on the ball dribbling agility results